2003
DOI: 10.1253/circj.67.951
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Thrombectomy Before Stent Implantation in Acute Myocardial Infarction

Abstract: hrombus formation after plaque rupture is the cause of vessel occlusion in acute myocardial infarction (AMI) and early, complete revascularization can salvage myocardium at risk and improve survival. 1 Primary angioplasty and stent implantation are important therapeutic options 2,3 and are associated with a higher reperfusion rate than pharmacological therapy alone. 4 However, these procedures can involve mobilization of thrombus and atheroma elements, causing distal embolization, the no-reflow phenomenon and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although some previous studies have shown that the coronary aspiration improves myocardial reperfusion in patients with STEMI (11)(12)(13), the issue of mechanical liberation of plaque debris induced by stent deployment remains unresolved. Moreover, it is still unclear which characteristics of the plaque cause distal embolization after stent deployment.…”
Section: Discussionmentioning
confidence: 99%
“…Although some previous studies have shown that the coronary aspiration improves myocardial reperfusion in patients with STEMI (11)(12)(13), the issue of mechanical liberation of plaque debris induced by stent deployment remains unresolved. Moreover, it is still unclear which characteristics of the plaque cause distal embolization after stent deployment.…”
Section: Discussionmentioning
confidence: 99%
“…4 5 Adjunctive intracoronary thrombectomy used in conjunction with primary PCI has recently emerged as an attractive tool to prevent distal embolisation in the microvasculature. [6][7][8][9][10] Recent studies showed that thrombectomy devices can preserve myocardial salvage and microvascular function. [11][12][13] On the other hand, reliable data on the application of these mechanical devices in STEMI and their additional benefits in reducing long term complications and clinical events are limited.…”
mentioning
confidence: 99%
“…Therefore, echocardiography at discharge improves the identification of those patients who will have benefit from pharmacological adjunctive treatment to attenuate microvascular dysfunction and augment myocardial blood flow in the reperfused myocardium. [16][17][18] …”
Section: Pathophysiology and Clinical Background Of Patients With Angmentioning
confidence: 99%